RANCANG BANGUN KENDALI LAMPU MENGGUNAKAN WEMOS D1 MINI DENGAN PUSAT KENDALI MEDIA SOSIAL TELEGRAM - Ihsan Kamil Teja Sumarna; Satrio Nugroho; Aldi Suryanto; Dolly Virgian Shaka Yudha Sakti (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2019)
Basic electricity tariffs are increasing and the number of uses of electrical equipment is one reason for every people to saving. One of the biggest contributors of electricity is lighting. Effective and efficient tools are needed to control the lights so that they can quickly and precisely turn on and off the lights. Light control using a microcontroller connected to the internet become solution in this study. Microcontroller on Wemos D1 Mini is used for the central system, while the social media telegram is the control application. Wemos D1 Mini is connected to the relay module to turn lights on and off. Wemos D1 Mini is connected to the internet via wifi so telegrams can communicate with it. A telegram account is made specifically as a bot to take orders from users who control electricity. The bot account is implanted on Wemos D1 Mini. The user's private telegram account is used to communicate with bot accounts. Users can turn on, turn off and view the lights conditions by giving commands to the bot account. The tools was testing to internet connection, in seven different locations and far away from it. Each location was conducted twelve experiments. From these experiments, the test results show the device works properly because there are no feature errors. The command to turn off, turn on and display the status of the lamp can be replied to properly. Need a good internet connection to get maximum results.